2020
DOI: 10.3390/ijms21062212
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Produced by the Oral Commensal Bacterium Corynebacterium durum Extend the Lifespan of Caenorhabditis elegans via SIR-2.1 Overexpression

Abstract: Human microbiota is heavily involved in host health, including the aging process. Based on the hypothesis that the human microbiota manipulates host aging via the production of chemical messengers, lifespan-extending activities of the metabolites produced by the oral commensal bacterium Corynebacterium durum and derivatives thereof were evaluated using the model organism Caenorhabditis elegans. Chemical investigation of the acetone extract of a C. durum culture led to the identification of monoamines and N-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Recent studies have found C. matruchotii and C. durum associated with health rather than caries [53][54][55]. Metabolites produced by C. durum have also been found to extend lifespan in the model organism Caenorhabditis elegans [56] and C. durum elicited no inflammatory response from human gingival and oral mucosal cells, suggesting it is a commensal [57]. S. cristatus has been shown to inhibit biofilm formation of the periodontal pathogen P. gingivalis by repression of virulence genes [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found C. matruchotii and C. durum associated with health rather than caries [53][54][55]. Metabolites produced by C. durum have also been found to extend lifespan in the model organism Caenorhabditis elegans [56] and C. durum elicited no inflammatory response from human gingival and oral mucosal cells, suggesting it is a commensal [57]. S. cristatus has been shown to inhibit biofilm formation of the periodontal pathogen P. gingivalis by repression of virulence genes [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…They play critical roles in regulating cellular metabolism, responses to oxidative stress, and lifespan through the deacetylation of histones and non-histones. 27 One report validated that TGS enhanced the resistance to oxidative stress and improved the mitochondrial functions through the activation of SIRT 1 in vitro. 28 SIR 2.1, the worm sirtuin homolog, is a protein deacetylase that depends on the cellular coenzyme nicotinamide adenine dinycleotied (NAD + ).…”
Section: Tgs Required Nrf2/skn-1 Activation To Extend the Lifespan Of C Elegansmentioning
confidence: 93%
“…Based upon our results, it appears as if there is either no active immunosuppressive mechanism employed by C. durum or this ability is regulated, since it would otherwise have been expected to function in each of the multispecies biofilm conditions. C. durum has not been investigated for its ability to modulate the immune response, but it has been shown to increase the longevity of Caenorhabditis elegans via the secretion of monoamines and N -acetyl monoamines ( Kim et al., 2020 ), suggesting that this species can influence the health of the host, as would be expected from a true commensal organism. We also previously demonstrated how S. sanguinis phagocytosis is inhibited by coculture with C. durum ( Treerat et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%